How to Successfully Patent Therapeutic Antibodies. (April 2015) - Lahrtz, Fritz
Therapeutic antibodies have become an established class of drugs for the treatment of a variety of diseases, especially cancer and autoimmune/inflammatory disorders, and a sufficient patent protection is a prerequisite for their successful commercialization. As monoclonal antibodies and their therapeutic potential have been well known for decades, the mere production of yet another therapeutic antibody is in many jurisdictions not considered a patentable invention. In contrast, antibodies with novel structural features and/or improved properties may be patentable. When drafting the claims, care should be taken to obtain a broad patent scope that protects both the antibody of interest and related antibodies having the same functional features, thereby preventing competitors from marketing a functionally equivalent antibody. Furthermore, the application should contain experimental evidence showing the improved properties of the claimed antibody. After the filing of a priority patent application, patent protection should be initiated at least in countries that are of particular commercial importance. Subsequent inventions relating to novel uses, formulations, dosage regimens, and combinations with other treatment modalities should be protected by further patent applications to extend patent term.